Categorial Conflict between Phrasal-Prepositional Verbs and Infinitives: The Great Complement Shift - Tjabaka-Mokapane, Lemohang (Universitas Lancang Kuning, 2023)
The development of grammatical forms and synchronic effects has captured a considerable interest of researchers across the globe. The research of this phenomenon is done to understand how certain linguistic forms arise and interact with other forms. Literature also discloses that a number of studies has addressed grammaticalisation of prepositions, which has somehow resulted in categorial conflict. However, there is dearth of literature that deals with /to/ to distinguish between phrasal-prepositional verbs and infinitives as a way of resolving the conflict. Again, some of the L2 students confuse complementation of /to/ in the phrasal-prepositional verb look forward to with that of the infinitives. They fail to draw a line of demarcation between the two constructions. Therefore, this qualitative study seeks to explore the status of /to/ in the phrasal-prepositional verb and infinitive clauses. It also identifies the category label of /to/ and describes its complementation. The study purposively and conveniently extracted data from Scott’s (2022) compilation of both application and cover letters. Following the Minimalist Program, the study reveals that /to/ in both the phrasal-prepositional verb and infinitives have gone through the process of grammaticalisation. It is noted that in the phrasal-prepositional verb, /to/ is still a preposition while in the infinitive clauses, it has gone through the great complementation shift known as decategorisation and extension, hence variation in category labelling. The study also presents that the structures of the phrasal-prepositional verb and the infinitive clauses vary based on the theory and concepts adopted. As a result, it is concluded that due to grammaticalisation of /to/ in both phrasal-prepositional verb and infinitive, their complementation differs.